Development of animal experimental periodontitis models - Do, Min-Jae (Korean Academy of Periodontology, 2013)
PURPOSE: An animal periodontitis model is essential for research on the pathogenesis and treatment of periodontal disease. In this study, we have introduced a lipopolysaccharide (LPS) of a periodontal pathogen to the alveolar bone defect of experimental animals and investigated its suitability as a periodontitis model. METHODS: Alveolar bone defects were made in both sides of the mandibular third premolar region of nine beagle dogs. Then, the animals were divided into the following groups: silk ligature tied on the cervical region of tooth group, Porphyromonas gingivalis LPS (P.g. LPS)-saturated collagen with silk ligature group, and no ligature or P.g. LPS application group as the control. The plaque index and gingival index were measured at 0 and 4 weeks postoperatively. The animals were then euthanized and prepared for histologic evaluation. RESULTS: The silk ligature group and P.g. LPS with silk ligature group showed a significantly higher plaque index at 4 weeks compared to the control (P<0.05). No significant difference was found in the plaque index between the silk ligature group and P.g. LPS with silk ligature group. The P.g. LPS with silk ligature group showed a significantly higher gingival index compared to the silk ligature group or the control at 4 weeks (P<0.05). Histologic examination presented increased inflammatory cell infiltration in the gingival tissue and alveolar bone of the P.g. LPS with silk ligature group. CONCLUSIONS: An additional P.g. LPS-saturated collagen with silk ligature ensured periodontal inflammation at 4 weeks. Therefore, P.g. LPS with silk ligature application to surgically created alveolar bone defects may be a candidate model for experimental periodontitis.